PERBANDINGAN KEMAMPUAN PENALARAN MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) DENGAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLANING PADA SISWA KELAS VII MTS NURUL HASANAH DESA SUNGAI GELAM KABUPATEN MUARO JAMBI - Relawati wati (Jurnal Math-UMB.EDU, 2019)
The comparison of students’ mathematics analogic through cooperative learning think talk write with students facilitator and learning model on class VII MTs NurulHasanahVelage Sungai Gelam districts Muaro Jambi. The comparasion of mathematics analogic through cooperative learning model think talk write with students’ facilitator and explaning learning model on class VII students’ of  MTs NurulHasanahVelage Sungai Gelam districts Muaro Jambi.Based on the observation in MTs NurulHasanahVelage Sungai Gelam districts Muaro Jambi, it is found that the mathematic analogi the students are on low category. It can be seen from the students ore on low category. It can be seen from the students test result. This happened because teacher was being so active in the class room, while the students put themselves only as the receiver of the learning material. Based on the problem research, the methode used in this research is experimental research because there is cause and effect between two variables. This research is located in MTs NurulHasanahVelage Sungai Gelam districts Muaro Jambi. The subject of the research is class VII studentsacademil year 2018/2019. The population of the students of class VII MTs NurulHasanahVelage Sungai Gelam districts Muaro Jambi.The result of the research show that the ability of the student in solving mathematics problem with cooperative learning model think talk write: 1) based on the post test, it can be seen that student test result in experimental class by using cooperative learning think type write is 33,7. While the result of control class by using student facilitator and explaining model is 29,9. Based on the result, it can be concluded that student ability in solving mathematics analogy by suing cooperative learning model think type write (ttw) is hinger than student who used student facilitator and explaining model on class vi student of MTs NurulHasanahVelage Sungai Gelam districts Muaro Jambi. Keywords: Mathematics reasoning, TTW, Student facilitaor and explaining